Chronic occupational diseases with short development periods in the in the Arctic zone of the Russian Federation - S.A. Syurin (Российская Арктика)
Along with the prevalence and severity of the course, the most important characteristic of a chronic occupational disease is the period of its formation, which, as a rule, exceeds 10 years. The aim of the study was to analyze the causes, structure and prevalence of occupational diseases that developed during shortened (no more than 10 years) periods of exposure to production hazards.